Estimation of Biomass and Competition Index in Pinus brutia Ten. Forests in Al-Qardaha Region _ Latakia Governorate (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Biological Sciences Series, 2026)
This study aimed to estimate the biomass and the effect of competition among trees in the Pinus brutia forests in the Al-Qardaha Region.Fieldwork was conducted across eight locations distributed throughout the Al_ Qardaha region, where forestry measurements were taken from 36 circular sample plots, each with an area of 400 m2, during the autumn of 2023.The diameter at breast height (1.3 m) and total height were measured for all trees in the sample plots. Additionally, the number of trees in each sample was counted, and the largest trees in the site were sampled to estimate the age.Biomass was calculated based on the diameter at breast height, and the Crown Competition Factor (CCF) index was calculated to estimate the impact of competition in the studied sites.The results of the study showed that the ages of the trees ranged between 42 and 56 years, while the average values for diameter at breast height ranged between 13 cm and 32.6 cm.Biomass values ranged between 873 ton\ hectare in the Qalila area and 100 tons\ hectare in the Dabbash area.The results indicated the presence of competition in only one site, where the CCF value reached 113.5%, while no great impact of competition was observed in the rest of the sites, where the index value was less than 100%.
Keywords: Pinus brutia Ten., Biomass, Competition index, Crown competition factor (CCF)